Uptake of Human Papilloma Vaccination in Uganda, Barriers and Opportunities - Kamulegeya, John (Uganda National Institute of Public Health, 2020)
Human papillomavirus (HPV) infection is the primary cause of cervical cancer. Cervical cancer is the leading cause of cancer deaths among women in Uganda and Sub Saharan Africa. HPV types 16 and 18 are responsible for about 70% of all cervical cancer cases worldwide. Vaccination against these prominent types of human papilloma virus has the potential to drastically reduce HPV-associated diseases, including cervical and other anogenital cancers. HPV vaccine against two sero types, 16 and 18 has been available for routine immunisation since 2014, targeting 10 year old girls using a two-dose schedule with an interval of six months between doses. However, HPV vaccination uptake is low with less than 50% of targeted girls receiving their 2nd follow up dose. A number of individual, community, and health system factors affect HPV vaccination. Multi prong strategies aimed at reaching younger girls, empowering the girl child and their parents /caretakers to demand for HPV vaccination services should be embraced in order to achieve high vaccination uptake in Uganda.
Keywords: Human Papilloma Vaccination; Uganda; Barriers; Opportunities